Performance damage characteristics of asphalt mixture suffered from the sulphate–water–temperature–load coupling action. Issue 5 (16th April 2022) - Xiong, Rui; Chu, Ci; Guan, Bowen; Sheng, Yanping
ABSTRACT: In order to evaluate the macro-mechanical performance of asphalt mixture suffered from the sulphate–water–temperature–load coupling action, the self-designed asphalt mixture dynamic water–salt attack apparatus was adopted for the accelerated simulation of real service conditions in sulphate enrichment environment. Splitting test at room temperature and low temperature was conducted for assessing the performance of asphalt mixture suffered from still water immersion and multi-factor coupling action. Then the performance damage characteristics of asphalt mixture under different conditions were explored. The multi-linear regression analysis and t-test were applied to determine the significance of factors on the performance of asphalt mixture. The performance deterioration mechanism of asphalt mixture exposed to dynamic water and sulphate attack was preliminarily analysed. The results show that the sulphate–water–temperature–load coupling action plays an important role in the macro-mechanical performance deterioration of asphalt mixture and dynamic water further accelerates the deterioration process of sulphate attack to asphalt mixture. The dynamic water scouring times, temperature and sulphate solution concentration have a significant impact on the performance of asphalt mixture. The decreasing adhesion between asphalt and aggregate, along with exterior/interior sulphate crystallisation erosion contributes the important inducement for the performance deterioration of asphalt mixture.